Yield and physiological quality of wheat seeds produced under different irrigation depths and leaf Silicon - Gama, Guilherme Fontes Valory (2021)
Water availability is one of the main factors responsible for wheat productivity, as well as the quality of the produced seeds. Silicon (Si) has an important role in mitigating the effects of various biotic and abiotic stresses. Thus, Si application can be used to mitigate the effects of different irrigation depths on the production and quality of wheat seeds. The work aimed to evaluate the yield and physiological quality of wheat seeds produced from plants fertilized with leaf Si and grown under different irrigation depths. The experiment was laid out in a split-plot randomized block design, with four replications. The plots consisted of three irrigation depths (0, 50, and 100% of the total irrigation requirement [TIR]). Si treatments were allocated (without application [0 mM] and 5 mM SiO2, applied at the tillering stage) in the subplots. The following parameters were evaluated: water balance of the system; soil moisture; yield; thousand seed weight; germination; electrical conductivity; accelerated aging; seedling length and emergence. The water balance of the system was negative for the 0% TIN irrigation depth after anthesis and there was less soil moisture in this irrigation depth. There was no effect of irrigation depths and Si application on plant yield. The smaller irrigation depths imposed reduced the thousand seed weight and increased the electrical conductivity of the seeds produced. Plants fertilized with Si did not differ in germination, but they produced more vigorous seedlings with greater growth and uniformity.